2004
DOI: 10.1080/00480169.2004.36437
|View full text |Cite
|
Sign up to set email alerts
|

Blood metabolites and body temperature of single calves between 1 and 4 days of age in a dairy herd in New Zealand

Abstract: The nutritional and thermal status of at least 90% of the calves was compatible with good health and survival during the first 4 days after birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…After birth, calves exhibit an initial decrease in body temperature caused by evaporation from the wet hair coat, followed by an increase in body temperature after the coat has dried (Vermorel et al, 1989b;Diesch et al, 2004a). Diesch et al (2004a,b) studied the physiological status of newborn dairy calves in New Zealand and found that calves born during cold (<10°C), wet, and windy weather conditions had lower rectal temperatures and took a longer time to stand up than calves born during warm and dry weather.…”
Section: Cold Stress and Heat Generationmentioning
confidence: 99%
“…After birth, calves exhibit an initial decrease in body temperature caused by evaporation from the wet hair coat, followed by an increase in body temperature after the coat has dried (Vermorel et al, 1989b;Diesch et al, 2004a). Diesch et al (2004a,b) studied the physiological status of newborn dairy calves in New Zealand and found that calves born during cold (<10°C), wet, and windy weather conditions had lower rectal temperatures and took a longer time to stand up than calves born during warm and dry weather.…”
Section: Cold Stress and Heat Generationmentioning
confidence: 99%
“…Furthermore, there was no evidence of an effect of time on the circulating BHB concentration in HOL or HOL-ANG calves ( p ≥ 0.19; Table 1 ). Measurements of BHB over the first week of life in calves are limited, but Diesch and colleagues [ 44 ] observed a decline in the circulating BHB concentration during the first 4 d of life. In general, the circulating BHB concentration in calves is considered an indicator of rumen development and the initiation of ruminal fermentation with the increased consumption of starter feeds over the first 6 weeks of life [ 45 , 46 ], and these changes are most notably observed around weaning [ 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%